Introduction: Visceral landscapes (the inside story). (13th April 2019) - Stroud, Christopher; Peck, Amiena; Williams, Quentin
Abstract : In this Special Issue, we bring together a collection of papers that develops a reading of linguistic landscapes through viscerals, that is, the gut, the heart, the liver and the stomach. We invite linguistic landscape studies (LLS) to ponder the usefulness and utility of psychology/cognition below the neck as yet another important dimension for understanding linguistic landscapes, and as a way to refine our approach to embodiment in linguistic landscapes specifically and in sociolinguistics more generally. The contributions to this Special Issue, from Qatar to Japan, push our understanding of social formations and how such formations emerge out of visceral readings of semiotic landscapes.